Psychological support and strategies for raising motivation in fresh students - Li, Tao; Pichugin, Vitaly; Shaknmalova, Irina; Ismailova, Nailya; Salimova, Svetlana (Frontiers in Psychology, 2023)
The goal of this study was to investigate the of fear of starting university training, determine its general characteristics, and test how providing psychological and motivational support for university enrollees may influence the elimination of this type of fear. The study used a random sample of 536 individuals, 268 participants each from one university in the Russian Federation and one from China, who were also randomly selected. Approximately equivalent experimental and control groups (134 people) were formed. The main experiment was conducted simultaneously for Chinese and Russian groups of participants under the same conditions. The modified Kessler psychological distress scale (K10) was used to measure fear of starting training 10 days before training and 2 days after. The experimental group received a special 7-step training to overcome fear and prepare for learning; results between groups and results before and after the start of training were compared using Student's t-test. Test scores for each participant were tested using Pearson's correlation to establish an association with the intervention for the majority of participants. In sum, the results of the carried out testing demonstrate a marked reduction in fear and stress after the start of training for both groups of both universities. Those students who have already experienced support show lower levels of fear of starting a course than those who have not received any help. The results of this study can be used to prepare university applicants for their future studies.